Pengaruh Kerja Part-time dan Manajemen Waktu Terhadap Prestasi Akademik Mahasiswa Universitas PGRI Wiranegara - Ajijah Ajijah; Sugeng Pradikto (Jurnal Manajemen Riset Inovasi, 2025)
This research seeks to explore how Part-Time Work and Time Management influence students' academic performance. A quantitative methodology was employed to investigate the relationship between the independent variables, part-time work and time management, and the dependent variable, academic achievement. The study focused on students from Universitas PGRI Wiranegara during the 2021–2024 period who are actively engaged in part-time work. The sample was selected using a probability sampling method, ensuring every student in the population had an equal chance of inclusion. Data collection was conducted through a questionnaire, which underwent validity and reliability testing. The findings revealed that part-time work significantly affects academic performance, with both positive and negative outcomes, depending on how well students manage their time. Additionally, effective time management proved to be a crucial factor in enhancing academic performance, even when students juggle their time between work and study. Further analysis indicated that both variables collectively have a meaningful impact on academic achievement. This research underscores the critical role of time management skills for students balancing work and study and highlights the importance of institutional support in helping students maintain this balance.